Nickel-copper diatomic catalyst and application thereof
By using nickel-copper diatomic catalysts in the electrocatalytic CO2 reduction process, the nickel and copper elements are dispersed in atomic order, and using hydroxylated carbon nanotubes as support, the existing catalysts have been solved, and the efficient and economical CO2 reduction effect has been achieved.
Patent Information
- Application Number
- CN202411538831.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-10-31
AI Technical Summary
Existing transition metal catalysts have poor selectivity and structural stability problems during the electrocatalytic CO2 reduction process, and are prone to corrosion, agglomeration or structural changes.
A nickel-copper diatomic catalyst was developed. The nickel and copper elements were dispersed in the catalyst framework on atomic scale, and hydroxylated carbon nanotubes were used as support to form a porous structure to improve catalytic performance.
It has achieved high Faraday efficiency (more than 98%) and high current density (160~240 mA/cm²) in a wide potential range, which significantly improves the selectivity and structural stability of the catalyst and reduces the preparation cost.
Smart Images

Figure CN119553307A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalytic materials and relates to a nickel-copper diatomic catalyst and application thereof. Background Art
[0002] Realizing efficient conversion of CO2 and promoting its resource utilization are important measures to achieve carbon emission reduction. Using CO2 as a carbon source and utilizing surplus electricity from new energy sources to reduce CO2 and produce organic compounds and fuels is a sustainable method to achieve local consumption of new energy electricity, stable storage across seasons, and carbon closure.
[0003] The products of electrocatalytic CO2 reduction are diverse, including single-carbon products such as CO and multi-carbon products such as acetic acid. The processes of preparing CO and collecting products are relatively simple and have high economic value. Therefore, in recent years, the field of electrocatalytic CO2 reduction to prepare CO has developed rapidly.
[0004] Studies have shown that catalysts based on precious metals such as gold and silver have good selectivity in the electrocatalytic reduction of CO2 to produce CO, but they are expensive, so transition metal elements (nickel, copper, iron, manganese, etc.) are widely used in the field of electrocatalytic CO2 reduction to produce CO. The practical problem is that in the process of electrocatalytic CO2 reduction, transition metal catalysts often face the problem of poor selectivity, and transition metal catalysts are prone to corrosion, agglomeration or structural changes during the electrocatalytic process.
[0005] In view of the above reasons, there is an urgent need to study a transition metal element catalyst that has a positive effect on the efficient conversion of CO2 and has economic value. Summary of the invention
[0006] In order to overcome the above problems, the present invention has developed a nickel-copper diatomic catalyst and its application, in which the nickel and copper elements are atomically dispersed in the catalyst skeleton, the catalyst skeleton is composed of metal ions and organic frames to form a metal organic framework, and hydroxylated carbon nanotubes are used as carriers. The nickel and copper elements are atomically dispersed in the catalyst skeleton, exposing abundant catalytic reaction activation sites, and the catalyst skeleton is supported by hydroxylated carbon nanotubes, which accelerates the electron transfer at the catalytic reaction interface and enhances the reaction current density. The nickel-copper diatomic catalyst exhibits excellent catalytic performance in the application of preparing carbon monoxide by electrocatalytic reduction of carbon dioxide, and has great commercial application potential.
[0007] Specifically, the purpose of the present invention is to provide the following aspects: In a first aspect, a nickel-copper diatomic catalyst is provided, wherein nickel and copper elements are dispersed in a catalyst skeleton at the atomic level, and the catalyst skeleton is composed of metal ions and an organic framework to form a metal-organic framework.
[0008] Wherein, the organic ligand is an imidazole ligand, and the metal ion is a zinc ion.
[0009] Wherein, the catalyst framework uses hydroxylated carbon nanotubes as carriers.
[0010] Wherein, the nickel-copper diatomic catalyst has a porous structure.
[0011] Among them, the Faradaic efficiency of the catalyst for electrocatalytic CO2 reduction to produce CO remains above 98% under a wide potential range of -0.2~-1.2V vs.RHE.
[0012] The nickel-copper diatomic catalyst has a current density of 160-240 mA / cm² when performing a carbon dioxide reduction reaction at a potential of -1.2 V relative to a reversible hydrogen electrode.
[0013] In a second aspect, a method for preparing the nickel-copper diatomic catalyst described in the first aspect is provided, characterized in that the method comprises: Step 1, preparing a precursor containing at least nickel element, copper element and hydroxylated carbon nanotubes; Step 2: carbonizing the precursor to obtain the nickel-copper diatomic catalyst.
[0014] In step 2, the carbonization temperature is 950-1100°C.
[0015] In a third aspect, a method for preparing fuel by electrocatalytic CO2 reduction is provided, wherein the fuel comprises the nickel-copper diatomic catalyst described in the first aspect or the nickel-copper diatomic catalyst prepared by the method described in the second aspect.
[0016] The beneficial effects of the present invention include: (1) In the nickel-copper diatomic catalyst provided by the present invention, nickel and copper elements are dispersed in the catalyst skeleton at the atomic level, exposing abundant catalytic reaction activation sites; the catalyst skeleton uses hydroxylated carbon nanotubes as carriers, which accelerates the electron transfer at the catalytic reaction interface and enhances the reaction current density.
[0017] (2) The nickel-copper diatomic catalyst provided by the present invention has a porous structure and has a strong adsorption effect on CO2 molecules.
[0018] (3) The nickel-copper diatomic catalyst provided by the present invention uses the transition metal nickel-copper elements as the reaction activation sites, avoiding the use of precious metals and significantly reducing the catalyst preparation cost.
[0019] (4) The preparation method of the nickel-copper diatomic catalyst provided by the present invention is simple, the reaction conditions are easy to control, and it is conducive to large-scale production, and has huge commercial potential and economic value.
[0020] (5) The preparation method of the nickel-copper diatomic catalyst provided by the present invention improves the electrocatalytic performance of the nickel-copper diatomic catalyst by adjusting the loading ratio of metal elements and hydroxylated carbon nanotubes. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] By reading the detailed description of the preferred specific embodiments below, various other advantages and benefits of the present invention will become clear to those of ordinary skill in the art. The drawings in the specification are only used for the purpose of illustrating the preferred embodiments and are not considered to be limitations of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For those of ordinary skill in the art, other drawings can also be obtained based on these drawings without creative work.
[0022] In the attached picture: Figure 1 The SEM characterization of the NiCu diatomic catalyst prepared in Example 1 is shown; Figure 2 A schematic diagram of the structure of a flow-type electrolytic cell for preparing CO by electrocatalytic reduction of CO2 using catalysts used in Example 1, Comparative Example 1 and Comparative Example 2 is shown; Figure 3 The CO Faraday efficiency diagram of the NiCu diatomic catalyst prepared in Example 1 is shown; Figure 4 The linear sweep voltammetry curves of the catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2 in CO2RR are shown; Figure 5 The linear sweep voltammetry curves of the NiCu diatomic catalysts prepared in Examples 1-4 in CO2RR are shown; Figure 6 The electrochemical impedance spectroscopy (EIS) curve of the NiCu diatomic catalyst prepared in Example 1 in CO2RR is shown. DETAILED DESCRIPTION
[0023] The following will refer to the attached Figures 1 to 6 Specific embodiments of the present invention are described in more detail. Although specific embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present invention and to fully convey the scope of the present invention to those skilled in the art.
[0024] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the difference in the functions of the components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" is an open term, so it should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the present invention, but the description is based on the general principles of the specification and is not intended to limit the scope of the present invention. The scope of protection of the present invention shall be determined by the attached claims.
[0025] In the description of the present invention, it should be noted that the terms "upper", "lower", "inner", "outer", "front", "rear", etc. indicate positions or positional relationships based on the working state of the present invention, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", "third", and "fourth" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.
[0026] To facilitate understanding of the embodiments of the present invention, further explanation will be given below by taking specific embodiments as examples in conjunction with the accompanying drawings, and each of the accompanying drawings does not constitute a limitation on the embodiments of the present invention.
[0027] On the one hand, according to a nickel-copper diatomic catalyst provided by the present invention, nickel elements and copper elements are dispersed at the atomic level in the catalyst skeleton, the catalyst skeleton is composed of metal ions and organic frameworks to form a metal organic framework, and hydroxylated carbon nanotubes are used as carriers.
[0028] Furthermore, the metal ion is preferably a zinc ion, and the organic ligand is preferably an imidazole ligand, that is, in this case, the catalyst skeleton is composed of zinc ions and imidazole ligands to form a zeolite imidazole framework.
[0029] In the present invention, zinc ions form stable metal-organic coordination compounds in the zeolite imidazole framework, and the good chemical stability and thermal stability make the catalyst not easy to deactivate during the reaction; the imidazole ring structure of the imidazole ligand has high chemical stability and can keep the structure unchanged under the reaction conditions; the zinc ions and the imidazole ligands form stable coordination compounds, and these coordination compounds serve as active sites for the catalytic reaction.
[0030] In the present invention, the nickel and copper elements are dispersed in the catalyst skeleton at the atomic level, exposing abundant catalytic reaction activation sites. The catalyst skeleton uses hydroxylated carbon nanotubes as carriers, which accelerates the electron transfer at the catalytic reaction interface and enhances the reaction current density.
[0031] In the present invention, the nickel-copper diatomic catalyst has a porous structure.
[0032] In the present invention, the nickel-copper diatomic catalyst has excellent catalytic performance, and the Faraday efficiency of the catalyst for electrocatalytic CO2 reduction to produce CO is maintained at more than 98% at a wide potential of -0.2~-1.2V vs.RHE.
[0033] Furthermore, when the nickel-copper diatomic catalyst performs a carbon dioxide reduction reaction at a potential of -1.2 V relative to a reversible hydrogen electrode, the current density is 160-240 mA / cm²; the nickel-copper diatomic catalyst has excellent CO2RR kinetics and mass transfer rate, and the charge transfer resistance is only 0.95 Ω.
[0034] On the other hand, according to the method for preparing the nickel-copper diatomic catalyst according to the first aspect provided by the present invention, the method comprises: Step 1, preparing a precursor containing at least nickel element, copper element and hydroxylated carbon nanotubes; Step 2: carbonizing the precursor to obtain the nickel-copper diatomic catalyst.
[0035] Specifically: Step 1: prepare a precursor containing at least nickel element, copper element and hydroxylated carbon nanotubes.
[0036] According to a preferred embodiment, step 1 comprises the following steps: Step 1-1, respectively preparing a hydroxylated carbon nanotube suspension, a solution A containing an imidazole derivative, and a solution containing at least Ni + and Cu 2+ Solution B; Step 1-2, mixing and stirring the hydroxylated carbon nanotube suspension, the solution A and the solution B to obtain a mixed solution; Step 1-3, washing and drying the mixed solution to obtain the precursor.
[0037] In step 1-1, the hydroxylated carbon nanotube suspension is obtained by the following steps: hydroxylated carbon nanotubes and a dispersant are mixed and ultrasonically mixed in a chemical solvent to form a hydroxylated carbon nanotube suspension.
[0038] According to the present invention, the dispersant is preferably a high molecular polymer, such as polyvinyl pyrrolidone, polyvinyl alcohol, polyacrylic acid, polyethylene glycol, etc., more preferably polyvinyl pyrrolidone.
[0039] The dispersant provides steric hindrance or charge repulsion to prevent the hydroxylated carbon nanotubes from attracting and agglomerating each other; and the hydroxylated carbon nanotubes are prone to agglomeration due to their high aspect ratio, and the dispersant suspends the hydroxylated carbon nanotubes in the dispersant by reducing the interfacial tension between the hydroxylated carbon nanotubes and the dispersant. The above dispersants all have a good effect of preventing the hydroxylated carbon nanotubes from agglomerating, and in particular, polyvinyl pyrrolidone can improve the compatibility between the hydroxylated carbon nanotubes and the dispersant in addition to the above effects, so that the hydroxylated carbon nanotubes are more easily dispersed in chemical solvents.
[0040] Furthermore, the mass ratio of the hydroxylated carbon nanotubes to the dispersant is (2-3): 1, preferably (2.4-2.6): 1, for example 2.5: 1. An appropriate ratio can help disperse the hydroxylated carbon nanotubes, and too much dispersant will affect the conductivity of the final NiCu diatomic catalyst.
[0041] According to the present invention, the chemical solvent may be an alcohol such as methanol, ethanol, propanol, isopropanol, or an ether such as dimethyl sulfoxide, dimethyl ether, tetrahydrofuran, preferably an alcohol, and more preferably ethanol.
[0042] The chemical solvent only needs to be well dispersed and not react with the hydroxylated carbon nanotubes, and all of the above chemical solvents have good dispersion effects. In particular, ethanol can dissolve chemical additives such as polyvinyl pyrrolidone and interact with the hydroxyl groups on the surface of the hydroxylated carbon nanotubes, thereby promoting the dispersion of the hydroxylated carbon nanotubes.
[0043] In the present invention, the total mass of the hydroxylated carbon nanotubes and the dispersant to the amount of the chemical solvent (mg:mL) is (1.5-5):1, preferably (2-4):1, for example 3.5:1. An appropriate amount of chemical solvent is conducive to the dispersion of the hydroxylated carbon nanotubes, while an excessive amount of chemical solvent may result in too low a concentration of the hydroxylated carbon nanotubes and is not conducive to the loading of the hydroxylated carbon nanotubes.
[0044] Furthermore, the ultrasonic time is 1 to 5 hours, preferably 2 to 4 hours, for example 2 hours.
[0045] Among them, the sound wave energy can be effectively transmitted during the ultrasonic treatment process, which helps to break the aggregation between the hydroxylated carbon nanotubes and make them evenly dispersed in the dispersant.
[0046] In step 1-1, the solution A containing the imidazole derivative is obtained by the following steps: dissolving the imidazole derivative in an organic solvent, followed by sonication to form the solution A.
[0047] In the present invention, the imidazole derivative is preferably 2-methylimidazole, which can be mixed with Zn(NO3)2·6H2O in metal nitrate hydrate to form a precursor ZIF-8, which is carbonized to form a porous nitrogen-carbon skeleton (i.e., zeolite imidazole framework) and is beneficial to the anchoring of nickel atoms and copper atoms.
[0048] In the present invention, the organic solvent is preferably methanol, which has strong solubility for imidazole derivatives, is conducive to the formation of precursors, and has low cost.
[0049] In the present invention, the concentration (mg / mL) of the imidazole derivative in the organic solvent is (70-80):1, preferably (75-80):1, and most preferably (78-79):1, for example 78.72:1. Within this range, it is not only beneficial for the organic solvent to fully dissolve the imidazole derivative, but also beneficial for the formation of the precursor.
[0050] Furthermore, at this time, the ultrasonic time is 10 to 30 minutes, preferably 12 to 20 minutes, for example 15 minutes.
[0051] The ultrasonic time does not need to be too long. If the time is too short, it will be unfavorable for the dispersion of the imidazole derivative in the organic solvent. If the ultrasonic time is too long, it is unnecessary. The above 10 to 30 minutes is more appropriate.
[0052] In step 1-1, the at least Ni + and Cu 2+ Solution B is obtained by the following steps: + and Cu 2+ The metal nitrate hydrate is dissolved in a polar solvent and subjected to ultrasound to obtain the solution B.
[0053] In the present invention, the at least Ni + and Cu 2+ The metal nitrate hydrate includes at least Ni(NO3)2·6H2O and Cu(NO3)2·3H2O, and also includes Zn(NO3)2·6H2O. At this time, Zn(NO3)2·6H2O provides zinc ions, which react with imidazole derivatives to obtain zeolite imidazole framework.
[0054] In the present invention, the molar ratio of Ni(NO3)2·6H2O, Cu(NO3)2·3H2O and Zn(NO3)2·6H2O is 1:2: (0~0.3) (excluding 0), preferably 1:2: (0.15~0.3), for example 1:2:0.2.
[0055] Among them, the above molar ratio can not only allow nickel and copper elements to be fully anchored in the precursor and expose a large number of catalytic activation sites, but also avoid excessive nickel and copper elements causing clustering and reducing the reaction activity of the nickel-copper diatomic catalyst.
[0056] In the present invention, the metal nitrohydrate can be completely dissolved in the polar solvent.
[0057] Furthermore, the polar solvent is preferably methanol.
[0058] Among them, methanol can not only dissolve metal nitrate hydrates to form a uniform solution; it also helps to remove crystal water from metal nitrate hydrates and promote the formation of anhydrous metal nitrates.
[0059] In the present invention, the total molar concentration of the metal nitrate hydrate in the polar solvent (mol / mL) is (6-9)×10 -5 :1, preferably (7~8)×10 -5 :1, for example 8×10 -5 :1, the amount of methanol solvent can fully dissolve the metal nitrate hydrate and is beneficial to the formation of the precursor.
[0060] Furthermore, at this time, the ultrasonic time is 10 to 30 minutes, preferably 12 to 20 minutes, for example 15 minutes.
[0061] In step 1-2, during mixing, the molar ratio of the metal nitrate hydrate to 2-methylimidazole is 1: (5~7), preferably 1: (6~6.5), for example 1: 6. 2-methylimidazole provides the required nitrogen-carbon skeleton, so that the nickel element and the copper element fully react with the 2-methylimidazole and anchor the metal element in the nitrogen-carbon skeleton to form a precursor, but excessive 2-methylimidazole will result in an excess of nitrogen-carbon skeleton in the formed precursor and insufficient activation sites for the reaction of nickel atoms and copper atoms, resulting in reduced catalyst performance.
[0062] In step 1-2, when mixed, the mass ratio of the metal nitrate hydrate to the hydroxylated carbon nanotubes is (31-92): 1, preferably (61-63): 1, for example 61.8: 1. A suitable mass of hydroxylated carbon nanotubes can enhance the reaction electron transfer and improve the catalytic performance, but excessive loading of hydroxylated carbon nanotubes will lead to insufficient exposure of the reaction activation sites of the nickel and copper elements, resulting in decreased catalytic performance.
[0063] In step 1-2, in order to obtain a uniform mixed solution, the stirring rate is 600-900 rpm, preferably 650-800 rpm, for example 700 rpm; the stirring time is 12-36 h, preferably 18-24 h, for example 24 h.
[0064] In steps 1-3, the detergent used for washing is preferably selected from methanol, ethanol, acetone or acetonitrile. More preferably, the detergent is consistent with the organic solvent selected for preparing solution A and the polar solvent selected for preparing solution B, for example, both are methanol. At this time, as few other materials as possible are introduced into the reaction system.
[0065] Furthermore, taking methanol as a detergent as an example, methanol can effectively remove unreacted metal ions and ligands; the surface of hydroxylated carbon nanotubes contains hydroxyl groups and has a certain polarity. Methanol, as a polar solvent, can better interact with the surface of hydroxylated carbon nanotubes and help remove impurities adsorbed on the surface; using methanol can also maintain the dispersion of the reaction system.
[0066] In step 1-3, centrifugation is used during washing to quickly obtain the desired substance. If the centrifugation speed is too slow, solid-liquid separation cannot be achieved; if the centrifugation speed is too fast, it is unnecessary and may even damage the instrument. Typically, the centrifugation speed is 8000-10000 rpm, such as 10000 rpm; the number of centrifugation times is 2-4 times, such as 3 times. After the centrifugation is completed, the precipitate is collected and dried.
[0067] In step 1-3, in order to avoid thermal decomposition caused by excessively high temperature during drying, the drying temperature is 50-70° C., for example, 60° C.; in order to remove moisture and excess solvent, the drying time is not less than 20 hours, for example, 24 hours.
[0068] Step 2: carbonizing the precursor to obtain the nickel-copper diatomic catalyst.
[0069] In step 2, the precursor is preferably ground into powder before carbonization so that the carbonization is evenly heated; the grinding time is 10 to 20 minutes, for example, 15 minutes.
[0070] In step 2, the carbonization includes: heating from room temperature to 950-1100°C at a heating rate of 1-10°C / min, keeping the temperature for 2-6 hours, and then naturally cooling to room temperature.
[0071] Among them, the higher carbonization temperature ensures the evaporation of zinc, and then replaces zinc with nickel and copper to anchor in the nitrogen-carbon skeleton, generating reaction activation sites, and successfully loading hydroxylated carbon nanotubes. The appropriate heating rate helps to evenly distribute the temperature inside and outside the material, ensuring the stability of the entire reaction system. The insulation stage provides enough time for the reaction to reach equilibrium and form a stable structure.
[0072] Further preferably, the carbonization comprises: heating from room temperature to 980-1050° C. at a heating rate of 2-5° C. / min, keeping the temperature for 3-5 h, and then naturally cooling to room temperature.
[0073] More preferably, the carbonization comprises: heating from room temperature to 1000°C at a heating rate of 3°C / min, keeping the temperature for 4 hours and then naturally cooling to room temperature.
[0074] In step 2, the carbonization is preferably carried out in an inert gas, which may be a rare gas such as argon, or nitrogen, preferably nitrogen which is cheap and readily available.
[0075] Furthermore, the flow rate of the inert gas is 80-120 mL / min, preferably 90-110 mL / min, for example 100 mL / min. The appropriate flow rate can ensure that the inert gas fills the furnace tube during the carbonization process to form a protective atmosphere to avoid oxidation, and can also avoid the accumulation of excessive inert gas in the furnace tube and the risk of explosion.
[0076] In step 2, the normal temperature is usually -10 to 40°C, for example 25°C.
[0077] In the present invention, the carbonization is preferably performed in a tube furnace.
[0078] In step 2, after carbonization, the obtained product is sequentially acid washed, alcohol washed, water washed, and dried to obtain the final product, a nickel-copper diatomic catalyst.
[0079] Among them, metal oxides, metal salts or other by-products will be formed during the carbonization process. These substances may cover the surface of the nickel-copper diatomic catalyst or exist in its structure. Acid washing can dissolve and remove these impurities, on the one hand to improve the purity of the nickel-copper diatomic catalyst, on the other hand to expose the active sites of the metal atoms; acid washing also helps to remove some of the bonds between metal atoms, thereby improving the dispersion of metal atoms on the surface of hydroxylated carbon nanotubes.
[0080] In step 2, the pickling process is + The concentration is 1~2 M, for example 1 M. This concentration is sufficient to effectively remove metal oxides and other impurities without causing a violent reaction.
[0081] In step 2, hydrochloric acid is preferably used for pickling. The hydrochloric acid reacts with the metal oxide to form soluble metal chlorides, thereby removing these impurities from the surface of the nickel-copper diatomic catalyst; hydrochloric acid is also easy to remove.
[0082] In step 2, the pickling time is 6 to 12 hours, preferably 8 hours. Long pickling time ensures that the process is sufficient so that impurities can be completely removed.
[0083] In step 2, pickling is preferably carried out at 60-90° C., for example 80° C., to accelerate the rate of the chemical reaction and improve the pickling efficiency without destroying the structure of the nickel-copper diatomic catalyst.
[0084] In step 2, the temperature is naturally lowered after the pickling is completed to reduce thermal shock and prevent changes in the structure of the nickel-copper diatomic catalyst.
[0085] In step 2, the alcohol washing is performed by methanol washing, the number of methanol washing is 2 to 4 times, the number of water washing is 2 to 4 times, after acid washing of excess impurities, then alcohol washing and water washing are performed in sequence until neutrality. In step 2, the drying temperature is 50 to 70 ° C, for example 60 ° C; the time is not less than 20 hours, for example 24 hours.
[0086] In another aspect, according to the present invention, a fuel is prepared by electrocatalytic CO2 reduction, wherein the fuel includes the nickel-copper diatomic catalyst described in the first aspect or the nickel-copper diatomic catalyst prepared according to the method described in the second aspect.
[0087] The present invention is further described below through specific examples, but these examples are merely exemplary and do not constitute any limitation to the scope of protection of the present invention.
[0088] Example 1
[0089] Disperse 30 mg of polyvinyl pyrrolidone and 75 mg of hydroxylated carbon nanotubes in 30 ml of anhydrous ethanol, and ultrasonicate for 2 hours to form a hydroxylated carbon nanotube suspension for later use; dissolve 7.872 g of 2-methylimidazole in 100 mL of methanol, and ultrasonicate for 15 min to obtain solution A for later use; dissolve 1.487 g of Zn(NO3)2·6H2O, 2.908 g of Ni(NO3)2·6H2O and 0.241 g of Cu(NO3)2·3H2O in 200 mL of methanol, and ultrasonicate for 15 min to obtain solution B for later use; The hydroxylated carbon nanotube suspension and solution B were mixed in solution A, and the mixture was continuously stirred at 700 rpm for 24 h at room temperature to obtain a mixed solution; the mixed solution was washed with methanol and centrifuged at 10000 rpm for 3 times, and the precipitate was collected and dried in a vacuum drying oven at 60° C. for 24 h to obtain a precursor; The precursor was ground for 15 min, and then heated from 25°C to 1000°C at a heating rate of 3°C / min in a tube furnace under a N2 atmosphere (100 mL / min), and then naturally cooled to room temperature 25°C after keeping warm for 4 hours; the carbonized product was acid-washed with 1 M hydrochloric acid solution at 80°C for 8 hours with stirring, and then washed with methanol and deionized water in sequence until neutral, and the precipitate was collected by centrifugation, and the precipitate was dried in a vacuum drying oven at 60°C for 24 hours to obtain a NiCu diatomic catalyst.
[0090] The SEM characterization of the final NiCu diatomic catalyst is as follows Figure 1As shown, it can be seen that the NiCu diatomic catalyst has a rich porous structure and a regular crystal configuration, and is loaded with a large amount of carbon nanotubes.
[0091] Example 2
[0092] Disperse 30 mg of polyvinyl pyrrolidone and 50 mg of hydroxylated carbon nanotubes in 30 ml of anhydrous ethanol, and ultrasonicate for 2 hours to form a hydroxylated carbon nanotube suspension for later use; dissolve 7.872 g of 2-methylimidazole in 100 mL of methanol, and ultrasonicate for 15 min to obtain solution A for later use; dissolve 1.487 g of Zn(NO3)2·6H2O, 2.908 g of Ni(NO3)2·6H2O and 0.241 g of Cu(NO3)2·3H2O in 200 mL of methanol, and ultrasonicate for 15 min to obtain solution B for later use; The hydroxylated carbon nanotube suspension and solution B were mixed in solution A, and the mixture was continuously stirred at 700 rpm for 24 h at room temperature to obtain a mixed solution; the mixed solution was washed with methanol and centrifuged at 10000 rpm for 3 times, and the precipitate was collected and dried in a vacuum drying oven at 60° C. for 24 h to obtain a precursor; The precursor was ground for 15 min, and then heated from 25°C to 1000°C at a heating rate of 3°C / min in a tube furnace under a N2 atmosphere (100 mL / min), and then naturally cooled to room temperature 25°C after keeping warm for 4 hours; the carbonized product was acid-washed with 1 M hydrochloric acid solution at 80°C for 8 hours with stirring, and then washed with methanol and deionized water in sequence until neutral, and the precipitate was collected by centrifugation, and the precipitate was dried in a vacuum drying oven at 60°C for 24 hours to obtain a NiCu diatomic catalyst.
[0093] Example 3
[0094] Disperse 30 mg polyvinyl pyrrolidone and 100 mg hydroxylated carbon nanotubes in 30 ml anhydrous ethanol, ultrasonicate for 2 hours to form a hydroxylated carbon nanotube suspension for later use; dissolve 7.872 g 2-methylimidazole in 100 mL methanol, ultrasonicate for 15 min to obtain solution A for later use; dissolve 1.487 g Zn(NO3)2·6H2O, 2.908 g Ni(NO3)2·6H2O and 0.241 g Cu(NO3)2·3H2O in 200 mL methanol, ultrasonicate for 15 min to obtain solution B for later use; The hydroxylated carbon nanotube suspension and solution B were mixed in solution A, and the mixture was continuously stirred at 700 rpm for 24 h at room temperature to obtain a mixed solution; the mixed solution was washed with methanol and centrifuged at 10000 rpm for 3 times, and the precipitate was collected and dried in a vacuum drying oven at 60° C. for 24 h to obtain a precursor; The precursor was ground for 15 min, and then heated from 25°C to 1000°C at a heating rate of 3°C / min in a tube furnace under a N2 atmosphere (100 mL / min), and then naturally cooled to room temperature 25°C after keeping warm for 4 hours; the carbonized product was acid-washed with 1 M hydrochloric acid solution at 80°C for 8 hours with stirring, and then washed with methanol and deionized water in sequence until neutral, and the precipitate was collected by centrifugation, and the precipitate was dried in a vacuum drying oven at 60°C for 24 hours to obtain a NiCu diatomic catalyst.
[0095] Example 4
[0096] Disperse 30 mg of polyvinyl pyrrolidone and 150 mg of hydroxylated carbon nanotubes in 30 ml of anhydrous ethanol, and ultrasonicate for 2 hours to form a hydroxylated carbon nanotube suspension for later use; dissolve 7.872 g of 2-methylimidazole in 100 mL of methanol, and ultrasonicate for 15 min to obtain solution A for later use; dissolve 1.487 g of Zn(NO3)2·6H2O, 2.908 g of Ni(NO3)2·6H2O and 0.241 g of Cu(NO3)2·3H2O in 200 mL of methanol, and ultrasonicate for 15 min to obtain solution B for later use; The hydroxylated carbon nanotube suspension and solution B were mixed in solution A, and the mixture was continuously stirred at 700 rpm for 24 h at room temperature to obtain a mixed solution; the mixed solution was washed with methanol and centrifuged at 10000 rpm for 3 times, and the precipitate was collected and dried in a vacuum drying oven at 60° C. for 24 h to obtain a precursor; The precursor was ground for 15 min, and then heated from 25°C to 1000°C at a heating rate of 3°C / min in a tube furnace under a N2 atmosphere (100 mL / min), and then naturally cooled to room temperature 25°C after keeping warm for 4 hours; the carbonized product was acid-washed with 1 M hydrochloric acid solution at 80°C for 8 hours with stirring, and then washed with methanol and deionized water in sequence until neutral, and the precipitate was collected by centrifugation, and the precipitate was dried in a vacuum drying oven at 60°C for 24 hours to obtain a NiCu diatomic catalyst.
[0097] Comparative Example 1 The catalyst was prepared in a similar manner to Example 1, except that no hydroxylated carbon nanotubes were added. The final product was named NiCu-NC diatomic catalyst. The specific steps were as follows: Dissolve 7.872 g of 2-methylimidazole in 100 mL of methanol and disperse by ultrasonic for 15 min to obtain solution A for later use; dissolve 1.487 g of Zn(NO3)2·6H2O, 2.908 g of Ni(NO3)2·6H2O and 0.241 g of Cu(NO3)2·3H2O in 200 mL of methanol and disperse by ultrasonic for 15 min to obtain solution B for later use; Solution B was mixed with solution A, and the mixture was continuously stirred at 700 rpm for 24 h at room temperature to obtain a mixed solution; the mixed solution was washed with methanol and centrifuged at 10000 rpm for 3 times, and the precipitate was collected and dried in a vacuum drying oven at 60° C. for 24 h to obtain a precursor; The precursor was ground for 15 min, and then heated from 25°C to 1000°C at a heating rate of 3°C / min in a tube furnace under a N2 atmosphere (100 mL / min), and then naturally cooled to room temperature 25°C after keeping warm for 4 hours; the carbonized product was acid-washed with 1 M hydrochloric acid solution at 80°C for 8 hours with stirring, and then washed with methanol and deionized water in sequence until neutral, and the precipitate was collected by centrifugation, and the precipitate was dried in a vacuum drying oven at 60°C for 24 hours to obtain a NiCu-NC diatomic catalyst.
[0098] Comparative Example 2 The catalyst was prepared in a similar manner to Example 1, except that hydroxylated carbon nanotubes and Cu(NO3)2·3H2O were not added. The final product was named Ni-NC single atom catalyst. The specific steps were as follows: Dissolve 7.872 g of 2-methylimidazole in 100 mL of methanol and disperse by ultrasonic for 15 min to obtain solution A for later use; dissolve 1.487 g of Zn(NO3)2·6H2O and 2.908 g of Ni(NO3)2·6H2O in 200 mL of methanol and disperse by ultrasonic for 15 min to obtain solution B for later use; Solution B was mixed with solution A, and the mixture was continuously stirred at 700 rpm for 24 h at room temperature to obtain a mixed solution; the mixed solution was washed with methanol and centrifuged at 10000 rpm for 3 times, and the precipitate was collected and dried in a vacuum drying oven at 60° C. for 24 h to obtain a precursor; The precursor was ground for 15 min, and then heated from 25°C to 1000°C at a heating rate of 3°C / min in a tube furnace under a N2 atmosphere (100 mL / min), and then naturally cooled to room temperature 25°C after keeping warm for 4 hours; the carbonized product was acid-washed with 1 M hydrochloric acid solution at 80°C for 8 hours with stirring, and then washed with ethanol, methanol and deionized water until neutral, and the precipitate was collected by centrifugation, and the precipitate was dried in a vacuum drying oven at 60°C for 24 hours to obtain a Ni-NC single atom catalyst.
[0099] The catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2 were respectively prepared into flow-type electrolytic cells, and electrode measurements were performed. Figure 2 The schematic diagram of the structure of the flow-type electrolytic cell for preparing CO by electrocatalytic reduction of CO2 is shown, and the flow-type electrolytic cell is composed of a cathode electrode, an anode electrode and a proton exchange membrane. The anode electrode is a nickel mesh; the proton exchange membrane is a Nafion 115 membrane, the reference electrode is an Ag / AgCl electrode of a saturated KCl solution, the cathode electrode, i.e., the working electrode, is a hydrophobic carbon paper with a microporous carbon layer, isopropanol is used as an organic solvent, and 5% Nafion 117 is used as a binder.
[0100] When preparing the cathode electrode, Example 1 and Comparative Examples 1-2 respectively prepared catalyst slurries according to the ratio of 3 mg catalyst, 500 μL isopropanol and 30 μL 5% Nafion117 (that is, the three catalyst slurries were: 3 mg NiCu diatomic catalyst prepared in Example 1, 500 μL isopropanol and 30 μL 5% Nafion117; 3 mg NiCu-NC diatomic catalyst prepared in Comparative Example 1, 500 μL isopropanol and 30 μL 5% Nafion117; 3 mg Ni-NC single atom catalyst prepared in Comparative Example 2, 500 μL isopropanol and 30 μL 5% Nafion117), the catalyst slurry was ultrasonicated for 0.5 hours, and then slowly dripped on the microporous layer side of the hydrophobic carbon paper of 1.5 × 1.5 cm using a pipette to form a catalytic layer, and the catalyst loading in the catalytic layer was approximately 1 mg cm -2 During the drop coating process, the slurry is evenly coated and dried in a dryer. The prepared catalyst-containing electrode carbon paper is then left to stand overnight at room temperature for use.
[0101] A 1.0 M KOH solution was used as the electrolyte for the cathode and anode electrodes, and a peristaltic pump was used to control the electrolyte flow at a rate of 50 mL min -1 The catalyst layer is continuously circulated in the cathode and anode chambers at a speed of 1.5, so that the catalyst layer is in contact with the flowing electrolyte. The effective geometric surface area of the electrode is 1 cm 2The flow rate of CO2 entering the cathode side is 50 sccm. During the test, the voltage applied to the cathode is -0.2~-1.2V vs.RHE. The CO2RR linear scanning voltammetry curve in this voltage range is recorded, and the gas product is passed into the gas chromatograph to test and analyze the Faraday efficiency of CO.
[0102] Figure 3 The CO Faraday efficiency diagram of the NiCu diatomic catalyst prepared in Example 1 is shown. It can be seen that the Faraday efficiency of the CO product remains above 98% at a wide potential range of -0.2 to -1.2 V vs. RHE, and the CO selectivity is very outstanding.
[0103] Figure 4 The linear sweep voltammetric curves of the catalysts prepared in Example 1, Comparative Example 1 and Comparative Example 2 in CO2RR are shown. It can be seen that the NiCu diatomic catalyst prepared in Example 1 is -1.2V vs. RHE, and the CO2RR reaction current density is 240 mA cm -2 , NiCu-NC diatomic catalyst prepared in comparative example 1 -1.2V vs.RHE, CO2RR reaction current density is 208mA cm -2 , Ni-NC single atom catalyst prepared in comparative example 2 -1.2V vs.RHE, CO2RR reaction current density is 160 mAcm -2 , Comparative Example 1 and Example 1 increased by 50% and 30% respectively compared with Comparative Example 2, indicating that by introducing Cu 2+ The loading of doped hydroxylated carbon nanotubes increases the reaction activation sites, enhances electron transfer, and significantly improves the catalytic performance of the catalyst.
[0104] Figure 5 The linear sweep voltammetric curves of the NiCu diatomic catalysts prepared in Examples 1-4 in CO2RR are shown, and it can be seen that the corresponding reaction current densities are 240 mA cm -2 , 161 mA cm -2 , 193 mA cm -2 , 170 mA cm -2 , indicating that the loading ratio of hydroxylated carbon nanotubes has a significant effect on the catalyst performance, especially the NiCu diatomic catalyst prepared in Example 1 has the most outstanding performance.
[0105] Figure 6 The electrochemical impedance spectroscopy (EIS) curve of the NiCu diatomic catalyst prepared in Example 1 in CO2RR is shown. The electrochemical impedance spectroscopy (EIS) curve is recorded in 1 M KOH electrolyte at -1.5 V, with an amplitude of 5 mV and a frequency range of 0.01 Hz to 10 5Hz. It can be seen that the NiCu diatomic catalyst prepared in Example 1 has excellent CO2RR kinetics and mass transfer rate, and the charge transfer resistance is only 0.95 Ω, which is due to the fact that the loading of hydroxylated carbon nanotubes promotes the electron transfer at the catalytic reaction interface.
[0106] The present invention is described in detail above in combination with preferred embodiments and exemplary examples. However, it should be noted that these specific embodiments are only illustrative explanations of the present invention and do not constitute any limitation on the protection scope of the present invention. Without exceeding the spirit and protection scope of the present invention, various improvements, equivalent substitutions or modifications may be made to the technical content of the present invention and its embodiments, which all fall within the protection scope of the present invention. The protection scope of the present invention shall be subject to the attached claims.
Claims
1. A nickel-copper diatomic catalyst, characterized in that: The nickel element and the copper element are dispersed in the catalyst skeleton at the atomic level. The catalyst skeleton forms a metal-organic framework with metal ions and organic ligands.
2. The nickel-copper diatomic catalyst according to claim 1, characterized in that: Preferably, the organic ligand is an imidazole ligand.
3. The nickel-copper diatomic catalyst according to claim 1, characterized in that: The metal ion is a zinc ion.
4. The nickel-copper diatomic catalyst according to claim 1, characterized in that The catalyst framework uses hydroxylated carbon nanotubes as carriers.
5. The nickel-copper diatomic catalyst according to claim 1, characterized in that: The nickel-copper diatomic catalyst has a porous structure.
6. The nickel-copper diatomic catalyst according to claim 1, characterized in that The Faradaic efficiency of the catalyst for electrocatalytic CO2 reduction to CO remains above 98% over a wide potential range of -0.2~-1.2V vs.RHE.
7. The nickel-copper diatomic catalyst according to claim 1, characterized in that When the nickel-copper diatomic catalyst performs a carbon dioxide reduction reaction at a potential of -1.2 V relative to a reversible hydrogen electrode, the current density is 160-240 mA / cm².
8. A method for preparing the nickel-copper diatomic catalyst according to any one of claims 1 to 7, characterized in that: The method comprises: Step 1, preparing a precursor containing at least nickel element, copper element and hydroxylated carbon nanotubes; Step 2: carbonizing the precursor to obtain the nickel-copper diatomic catalyst.
9. The method according to claim 8, characterized in that In step 2, the carbonization temperature is 950-1100°C.
10. An electrocatalytic CO2 reduction method for preparing fuel, characterized in that: The fuel comprises the nickel-copper diatomic catalyst described in any one of claims 1 to 7 or the nickel-copper diatomic catalyst prepared by the method described in any one of claims 8-9.
Citation Information
Patent Citations
Preparation of MOF-based hydroxylated magnetic nitrogen-doped carbon nanotubes, and uses in detection of auxin content in tea leaves
CN111036184A
Monatomic catalyst and application thereof
CN112156802A
Catalyst for electrocatalytic carbon dioxide reduction reaction as well as preparation method and application of catalyst
CN113403644A
Copper-based catalyst, copper-based catalytic electrode, preparation method of copper-based catalyst and preparation method of copper-based catalytic electrode and electrochemical electrolysis device
CN115821318A
Iron-cobalt diatomic catalyst applied to oxygen reduction reaction as well as preparation method and application of iron-cobalt diatomic catalyst
CN116826085A